1991
DOI: 10.1007/bf01986568
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of arachidonic acid metabolism by orally administered morniflumate in man

Abstract: Unlike other classic NSAIDs, some fenamates given at therapeutic concentrations, have been shown to inhibit, both in vitro and in vivo, the 5-lipoxygenase pathway of arachidonic acid cascade as well as the synthesis of cyclooxygenase products. This dual inhibitory property might represent an improvement in anti-inflammatory therapy. The aim of this work was to characterize the effect of morniflumate, administered at therapeutic dosages to normal human volunteers, on leukotriene B4 (LTB4) and thromboxane (TXB2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…An inhibitory effect on cyclooxygenase has been attributed to NA (34). We have studied the effect of another inhibitor of prostaglandin synthesis, indomethacin, on IL-13-induced asthma reaction, and indomethacin failed to attenuate the airway response to IL-13.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An inhibitory effect on cyclooxygenase has been attributed to NA (34). We have studied the effect of another inhibitor of prostaglandin synthesis, indomethacin, on IL-13-induced asthma reaction, and indomethacin failed to attenuate the airway response to IL-13.…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences in baseline values of airway pressure among the control, IL-13 instillation alone, and IL-13 plus NA groups. We conclude that NA inhibited not only goblet cell hyperplasia but also AHR and eosinophilic inflammation induced by IL- 13. It has been reported that NA has an inhibitory effect on cyclooxygenase (34). We studied the effect of indomethacin on IL-13-induced airway responses.…”
Section: Effects Of Na On Ahr and On Eosinophils In Balf After Il-13mentioning
confidence: 99%
“…In the present study, we introduced a simple analytical method to quantify LOX and COX products in HWB. As shown previously [16,21] stimulation of blood ex vivo and the evaluation of metabolites from AA represent a valuable model for the assessment of the in vivo efficiency of drugs acting on AA metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…ACBs used in this work also inhibit cycloxygenases and lipoxygenases that participate in arachidonic acid metabolism [Civelli et al, 1991] and the 3␣-hydroxysteroid dehydrogenase involved in sex steroid metabolism [Penning et al, 1985]. Metabolites of the lipoxygenase, and cycloxygenase pathways positively modulate cation and anion channels [Diener et al, 1996;Kanli and Norderhus, 1998].…”
Section: Discussionmentioning
confidence: 99%